Populační genetika zimovišť druhového komplexu Pipistrellus pipistrellus - Habalová, Kateřina (Univerzita Karlova, Přírodovědecká fakulta, 2020)
This thesis deals with two cryptic pipistrelle bat species, common pipistrelle (Pipistrellus pipistrellus) and soprano pipistrelle (Pipistrellus pygmaeus) living in sympatry in continental Europe. Although both species are abundant during summer in Europe, they spent winter in mass hibernacula and there is only limited knowledge about this period. In total, 233 individuals from four mass hibernacula were sampled in Central Europe and Romania. The species composition and population variability in winter hibernacula was examined by using the tools of population genetics (analysis of mitochondrial sequences and nuclear microsatellites). Two hibernacula with exclusive or partial mass representation of soprano pipistrelle were genetically confirmed for the first time. No cytonuclear conflict neither admixed nuclear genotype was detected, that means that early stage of hybridization between both species was not revealed. Similar genetic structure in both genetic markers indicate, that swarming and hibernating populations are substantially overlapping. Compared to the P. pygmaeus, higher genetic variability was found in P. pipistrellus populations, even though genetic variability is relatively low compared to other species. It can be caused by strong gene flow, in the case of P. pygmaeus it may be caused. Tato práce se zabývá dvěma kryptickými druhy, netopýrem hvízdavým (Pipistrellus pipistrellus) a netopýrem nejmenším (Pipistrellus pygmaeus) žijícími v kontinentální Evropě v sympatrii. I přesto, že jsou oba druhy přes léto v Evropě hojné, na zimu se stahují na masová zimoviště, kterých je známých pouze několik. Bylo získáno celkem 233 jedinců obou druhů ze čtyř masových zimovišť z oblasti střední Evropy a Rumunska a pomocí nástrojů populační genetiky (analýza mitochondriálních sekvencí a jaderných mikrosatelitů) byla zkoumána druhová skladba a variabilita populací na zimovištích. Poprvé byla pomocí genetických nástrojů potvrzena dvě hibernakula s výlučným či podstatným masovým zastoupením netopýra nejmenšího. Nebyl ...